PESAN DAKWAH SUNAN DRAJAT DALAM WEJANGAN CATUR PIWULANG: Analisis Semiotika Charles Sanders Pierce - Ainur Rofiq; Abdur Rozaq (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2023)
Islam is a religion that calls on its followers to carry out da'wah through various methods, one of which is Sunan Drajat who preaches through the teachings of Catur Piwulang (four teachings). This discourse contains many preaching messages if examined further. Therefore, researchers want to know more deeply about the preaching contained in it by analyzing the preaching. This research aims to: Find out the results of the analysis of Catur Piwulang's discourse using Charles Sanders Pierce's Semiotic Theory, as well as to find out the da'wah message contained. This research uses descriptive qualitative research. The researcher uses Charles Sanders Pierce's semiotic analysis research approach to dissect the discourse of "Catur Piwulang" by Sunan Drajat. Semiotic analysis is used to see how the representament, object, interpretant are in this discourse, as well as to find out the preaching messages contained in it. The data collection techniques used in this research are observation and documentation. Based on the results of the analysis in the "Catur Piwulang" discourse, the researchers obtained the results, 1) The type of da'wah message contained in the "Catur Piwulang" discourse contains moral messages that teach related to human nature or behavior in life. 2) The results of the semiotic theory analysis of the discourse "Catur Piwulang" have the meaning of helping others.